DEHIDRASI KATALITIK MINYAK JARAK DENGAN DISERTAI PENGALIRAN GAS - Taufik Iskandar (Universitas Tribhuwana Tunggadewi, 2011)
Dehydration to be run by heating castor oil and of natrium sulphate hydrogen at temperature, certain time is at the same time swirled and emited a stream of by carbon gas of dioxid. Result of which is to determined by its iodine number, sour number, viscosity, diffraction index, specific gravity and colour. Situation of good process is usage 0,946 gmol; 100 g castor oil; NaHSO4 3% from oil weight, temperature 1900C, time 45 castor oil amount and minute 100 g, for gourd 500 cc. biggest and time reaction of. Iodine number which have been reached 181,5 or increase of iodine number 98,3 from its value in oil initialy